Habitat Characteristics Supporting Bird Species Richness in Mid-Field Woodlots - Dvořáková, Lenka; Kuczyński, Lechosław; Rivas-Salvador, Javier; Reif, Jiří (Frontiers in Environmental Science, 2022)
Farmland biodiversity has undergone drastic declines due to agricultural intensification during the last decades. To prevent further biodiversity loss, the maintenance and restoration of non-productive habitats is essential. Woodlots, small patches of woody vegetation in agricultural landscapes, are one such habitat that are currently subsidized by the European Union’s Common Agricultural Policy (EU’s CAP). For effective implementation, however, it is necessary to assess what habitat characteristics are the most beneficial for biodiversity. Our study performs such an assessment using birds as model organisms. Specifically, we related characteristics of various woodlots to (I) the species richness of all birds, and (II) the species richness of both forest and farmland birds – groups with different ecological requirements. For this purpose, we counted birds (27 farmland and 26 forest species) and measured habitat characteristics (describing vegetation structure, diversity and nativeness) and spatial characteristics (area, shape and isolation) in 82 mid-field woodlots (0.76‒1.25 ha, average 0.46 ha) in the Czech Republic (Central Europe). After accounting for the effects of spatial characteristics, overall bird species richness increased with vegetation height and woody plant species richness. In addition, richness showed a non-linear decrease with the cover of an invasive tree, the Black Locust Robinia pseudoaccacia. Interestingly, forest bird species richness was related to the same habitat characteristics as the overall bird species richness. By contrast, farmland bird species richness was positively related to the diversity of woodlot microhabitats, which reflects mainly enrichment by non-forest sites such as grassland or sparse shrubs. Our results indicate that the ecological performance of habitat characteristics (and not only the woodlot area) is important for the restoration of bird diversity in woodlots, and as such should be taken into consideration by the EU’s CAP subsidy system. Moreover, if woodlot management aims to maximize the overall bird diversity ‒ a common practice in biodiversity conservation ‒ our results show that current practices may favor widespread forest bird species, but not the farmland birds that are more threatened in Europe. To manage the woodlot habitat for farmland birds, we suggest that microhabitat heterogeneity should be maximized.